Field characterization of wave-induced underwater light field fluctuations - Gernez, P.; Antoine, David (Wiley-Blackwell, 2009)
A field characterization of the amplitude and periods of the underwater light fieldfluctuations is presented on the basis of field measurements of the downward and upwardirradiances at a deep-sea mooring in the Mediterranean Sea (BOUSSOLE site). Theoptical time series at this site includes multispectral irradiance measurements at two depthsand irradiance profiles taken from free-fall radiometers. It is already several years longand is paralleled by a time series of wind and waves. When pooled together, both data setsprovide an opportunity to complement previous field experiments dedicated to theunderstanding of underwater light fluctuations, which were mostly carried out in coastalwaters and essentially for the downward irradiance, by exploring more systematically theelectromagnetic spectrum and the range of environmental parameters. In addition, thecharacteristics of the upward flux are also investigated. The behavior of the amplitude andperiod of the Ed fluctuations are coherent with previous findings, although a more globalpicture is provided. The conditions for maximum fluctuations under clear skies arefor wave heights of 0.5 m or wind speeds between 1 and 5 m s1. Fluctuations arereduced under clear skies for wave heights >1.5 m or for wind speeds >7 m s1. Thedominant periods of the fluctuations in the upward flux are changing in parallel to those inthe downward flux. The amplitude of the fluctuations in the upward flux is, however,evolving in the opposite direction as compared to the downward flux, e.g., decreasingwhen the water becomes clearer.